2019
DOI: 10.1016/j.cub.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Neural Signatures of Prediction Errors in a Decision-Making Task Are Modulated by Action Execution Failures

Abstract: Highlights d Humans devalue choices less following execution versus selection errors d Reward prediction errors in the striatum are attenuated following execution errors d Different error classes have distinct neural signatures

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
2
21
2
Order By: Relevance
“…A recent fMRI experiment using a similar 3-arm bandit task to the one employed here, revealed an attenuation of the signal associated with negative reward prediction error in the striatum following execution failures (McDougle et al, 2019). Our observation of a larger negative deflection for execution error trials in the MFN may appear contrary to these previously reported striatal results.…”
Section: Differential Error Processing Indexed By the Mfncontrasting
confidence: 93%
See 4 more Smart Citations
“…A recent fMRI experiment using a similar 3-arm bandit task to the one employed here, revealed an attenuation of the signal associated with negative reward prediction error in the striatum following execution failures (McDougle et al, 2019). Our observation of a larger negative deflection for execution error trials in the MFN may appear contrary to these previously reported striatal results.…”
Section: Differential Error Processing Indexed By the Mfncontrasting
confidence: 93%
“…Overall, this bandit was chosen on 39.49% (±9.38) of the trials, which was significantly greater than the Low Execution/High Selection error bandit (29.01%; ±6.89%, p < .001) and Neutral bandit (31.50%; ±8.64%, p = .046), with no difference for the latter two (p = .877). Consistent with previous work, when expected value is equal, participants prefer choices in which unrewarded trials are attributed to errors in movement execution rather than errors in action selection (Wu et al, 2009;Green et al, 2010;McDougle et al, 2016;Parvin et al, 2018;McDougle et al, 2019).…”
Section: Experiments 2: Behavioral Responsessupporting
confidence: 85%
See 3 more Smart Citations